Global attractor for a class of nonlinear generalized Kirchhoff models - Lv, Penghui; Lu, Jingxin; Lin, Guoguang (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
The paper studies the long time behavior of solutions to the initial boundary value problem(IBVP) for a class of Kirchhoff models flow .We establish the well-posedness, the existence of the global attractor in natural energy space